Re-establishment of Drosera spiralis (Droseraceae), and a new circumscription of D. graminifolia - Gonella, Paulo Minatel; Rivadavia, Fernando; Sano, Paulo Takeo (Phytotaxa, 2012)
Drosera graminifolia and D. spiralis have long been considered conspecific, but new morphological and ecological data support the recognition of these taxa as distinct species. Both species are here described and illustrated, including observations on ecology, habitat, and conservation status, together with a distribution map, line drawings, photographs, and a table containing the distinctive characters.